A Numerical Study on Co-Extrusion to Produce Coaxial Aluminum-Steel Compounds with Longitudinal Weld Seams - Bernd-Arno Behrens (Metals, 2018)
The use of lightweight materials is one possibility to limit the weight of vehicles and to reduce CO2 emissions. However, the mechanical properties and weight-saving potential of mono-materials are limited. Material compounds can overcome this challenge by combining the advantages of different materials in one component. Lateral angular co-extrusion (LACE) allows the production of coaxial semi-finished products consisting of aluminum and steel. In this study, a finite element model of the LACE process was built up and validated by experimental investigations. A high degree of agreement between the calculated and experimentally determined forces, temperatures, and the geometrical shape of the hybrid profiles was achieved. In order to determine suitable parameters for further extrusion experiments, the influence of different process parameters on material flow and extrusion force was investigated in a numerical parametric study. Both the temperature and extrusion ratio showed a significant influence on the occurring maximum extrusion force as well as the material flow inside the LACE tool. The maximum force of 2.5 MN of the employed extrusion press was not exceeded. An uneven material flow was observed in the welding chamber, leading to an asymmetric position of the steel rod in the aluminum matrix.